ANTI RADIATION BUILDING DESIGN: LOCAL SAND TYPE ANALYSIS TO GET CONCRETE X-RADIATION RESISTANT X-RAY - Muhammad Fakhrurreza; Fisnandya Meita Astari (Poltekkes Kemenkes Semarang, 2019)
Background : There are three ways to protect yourself from the danger of radiation, namely by regulating the length of irradiation (the effect of time), the use of anti-radiation material (shielding), and adjusting the distance from the radiation source (distance). In order to be safe in carrying out x-ray irradiation, patients and operators must take three steps so that radiation hazards can be minimized (Nunung, 2004). One way to check the danger of external radiation is to use a radiation barrier. This method is generally preferred, because it creates safe working conditions. Besides that the time and distance factors can be monitored continuously at the time of work, so that radiation workers can be guaranteed safety.Methods: This research is quantitative research with an experimental approach. The method of data collection in this study is observation, direct experiments and documentation. The types of sand to be used in this study are south beach sand, opaque sand, progo sand, white mountain sand and volcanic sand.Result : Concrete using sand material from South Beach has the lowest HVL value of 0.8644cm. Conclusion :The HVL value possessed by concrete with South Beach sand material is most effective in resisting x-ray radiation.